2017
DOI: 10.1186/s12955-017-0779-5
|View full text |Cite
|
Sign up to set email alerts
|

Intensive follow-up for women with breast cancer: review of clinical, economic and patient’s preference domains through evidence to decision framework

Abstract: BackgroundWomen treated for breast cancer are followed-up for monitoring of treatment effectiveness and for detecting recurrences at an early stage. The type of follow-up received may affect women’s reassurance and impact on their quality of life. Anxiety and depression among women with breast cancer has been described, but little is known about how the intensity of the follow-up can affect women’s psychological status. This study was undertaken to evaluate the effects of intensive vs. less-intensive follow-up… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 51 publications
0
24
0
4
Order By: Relevance
“…Similarly, imaging for follow-up of patients with early breast cancer and metastatic patients may be delayed if necessary, with tailoring of radiological assessments per symptoms or other suspicion of progression, as clinically assessed-while still preferring telemedicine for non-priority complains and interventions. 21 prIorItIes for breast surgICal onCology Cancer surgery is one of the cancer interventions bringing the greatest benefits for patients with cancer, principally in the curative setting, resulting in gains in cancer survival. 22 The priority-setting framework of breast cancer surgery aims to understand how reasonably and for how long cancer surgery can be delayed, assuring the attainment of the highest standards for quality care delivery.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, imaging for follow-up of patients with early breast cancer and metastatic patients may be delayed if necessary, with tailoring of radiological assessments per symptoms or other suspicion of progression, as clinically assessed-while still preferring telemedicine for non-priority complains and interventions. 21 prIorItIes for breast surgICal onCology Cancer surgery is one of the cancer interventions bringing the greatest benefits for patients with cancer, principally in the curative setting, resulting in gains in cancer survival. 22 The priority-setting framework of breast cancer surgery aims to understand how reasonably and for how long cancer surgery can be delayed, assuring the attainment of the highest standards for quality care delivery.…”
Section: Introductionmentioning
confidence: 99%
“…Although current guidelines [4,5,19] and systematic review [9,25] do not recommend routine imaging for patients with breast cancer, real-word practices often involve the use of advanced imaging studies owing to the belief that earlier detection of distant metastasis may lead to improved survival [15,16,26,27]. Moreover, diagnostic studies for distant metastasis may provide emotional support and reassurance to both the physician and patient [6,[28][29][30].…”
Section: Discussionmentioning
confidence: 99%
“…There is no evidence that the detection of asymptomatic distant metastases leads to a longer survival 32. Some data indicated that the detection of isolated loco-regional or contra-lateral breast cancer recurrences in patients without symptoms has beneficial impact on survival of breast cancer patients when compared to late symptomatic detection33; however, it was shown that only 40 % of the isolated loco-regional recurrences in asymptomatic patients were detected during routine examination 34.…”
Section: Discussionmentioning
confidence: 99%